Insights into metal ion binding in phospholipases A(2): ultra high-resolution crystal structures of an acidic phospholipase A(2) in the Ca2+ free and bound states - Murakami, M. T.; Gabdoulkhakov, A.; Genov, N.; Cintra, A. C. O.; Betzel, C.; Arni, R. K. (Elsevier B.V., 2006)
The electrophile Ca2+ is an essential multifunctional co-factor in the phospholipase A(2) mediated hydrolysis of phospholipids. Crystal structures of an acidic phospholipase A(2) from the venom of Bothrops jararacussu have been determined both in the Ca2+ free and bound states at 0.97 and 1.60 angstrom resolutions, respectively. In the Ca2+ bound state, the Ca2+ ion is penta-coordinated by a distorted pyramidal cage of oxygen and nitrogen atoms that is significantly different to that observed in structures of other Group I/II phospholipases A(2). In the absence of Ca2+, a water molecule occupies the position of the Ca2+ ion and the side chain of Asp49 and the calcium-binding loop adopts a different conformation. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: snake venom; phospholipase A(2); Ca2+ coordination; anticoagulant activity; X-ray analysis